Strengthening Legislative Capacity: An Analysis of Expert Staff Professionalism in Indonesia's House of Representatives - Pesta Evaria Simbolon; Sunarto Sunarto; Khasan Effendy; T. Herry Rachmatsyah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The professionalism of expert staff in the Indonesian House of Representatives (Dewan Perwakilan Rakyat Republik Indonesia (DPR RI) Republik Indonesia) is influenced by various interrelated factors, including work management, coordination, compensation, qualifications, and competencies. This study aims to identify the key factors affecting the professionalism of Dewan Perwakilan Rakyat Republik Indonesia (DPR RI) expert staff and to provide recommendations for improving their performance. A qualitative research design was employed using a thematic approach, grounded theory, and triangulation, with data obtained from interviews and documents analyzed through NVIVO 14 ( ). The findings reveal that professionalism is primarily shaped by effective work management and coordination, competitive compensation, adequate qualifications and competencies, rigorous recruitment and selection processes, and objective performance evaluations. Furthermore, continuous professional development and clear career pathways significantly enhance staff loyalty and performance. Benchmarking against industry standards also provides insights into best practices that can be adopted. In addition, a well-defined organizational structure and effective strategies to address workplace challenges help clarify roles and responsibilities. High-quality support from expert staff and satisfaction with compensation directly contribute to the effectiveness of members and leaders of the Indonesian House of Representatives (DPR RI) parliamentary bodies. These findings imply that the Indonesian House of Representatives (DPR RI) needs to strengthen these strategic factors to ensure maximum efficiency and effectiveness of expert staff, ultimately enhancing the overall performance of the institution.